Family Support on Breastfeeding Self-Efficacy Among Pregnant Women - Astuti, Yuni; Sustiwi, Hesti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Breast milk has a complete content of nutrients that benefit the baby. The process of breastfeeding is impacted by the mother's self-efficacy. High maternal confidence in breastfeeding increases breastfeeding success. The self-efficacy of the mother can be influenced by family support. The mother's confidence in breastfeeding could increase with support with care and knowledge. The aim of this study is to evaluate the correlation between family support and self-efficacy in breastfeeding. The cross-sectional research design for descriptive studies. 91 pregnant women who were in their third trimester and had no pregnancy complications made up the sample. A family support survey and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) instrument were both used as research instruments. Using Spearman's rho correlation, analyze the data. According to this study, 71 persons (78%) fall into the "good" category for family support, and 82 (89%) fall into the "high" category for breastfeeding self-efficacy. The analysis's findings showed a relationship between pregnant women's breastfeeding self-efficacy and family support, with a p-value of 0.0001 (p less than 0.05) and with a correlation coefficient of r=0.549. Good family support increases the likelihood that a woman will successfully breastfeed. Family involvement in the practice may increase the mother's confidence in breastfeeding. Abstrak: ASI memiliki kandungan zat gizi lengkap yang bermanfaat bagi bayi. Self-efficacy ibu berpengaruh terhadap proses memnyusui. Kepercayaan ibu yang tinggi terhadap proses menyusui meningkatkan keberhasilan pemberian ASI. Self-efficacy ibu dapat dipengaruhi oleh dukungan keluarga. Dukungan lingkungan sekeitar mampu menambah kepercayaan diri ibu dalam proses pemberian ASI. Studi ini untuk mengetahui dukungan keluarga terhadap breastfeeding self efficacy ibu hamil. Desain penelitian menggunakan pendekatan cross-sectional. Responden penelitian sebanyak 91 yang berada pada trimester ketiga dan tidak memiliki komplikasi kehamilan. Kuesioner yang digunakan dalam penelitian ini BSE-SF untuk mengukur self-efficacy sedangkan dukungan keluarga menggunakan kuesioner dukungan keluarga yang dikembangkan peneliti, Uji analisis menggunakan Spearman’s rho. Hasil studi menunjukkan sebagian besar ibu hamil memiliki dukungan keluarga yang baik (78%), dan self-efficacy yang tinggi (89%). Uji korelasi menunjukkan bahwa dukungan keluarga berhubungan dengan breastfeeding self-efficacy (p value = 0,0001). Ibu hamil dengan dukungan keluarga yang baik maka memiliki breastfeeding self efficacy yang tinggi. Keterlibatan keluarga dalam proses menyusui dapat meningkatkan kepercayaan diri ibu untuk menyusui.